Some obligatory conditions and generalizations of the Fedorov theorem - Polovitskii, Ya. D. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We introduce a new type of conditions, S-obligatory conditions. We describe broad classes of groups with the Chernikov obligatory condition and some other conditions similar to the known Fedorov condition.